2017
DOI: 10.1093/ecco-jcc/jjx109
|View full text |Cite
|
Sign up to set email alerts
|

Research Gaps in Diet and Nutrition in Inflammatory Bowel Disease. A Topical Review by D-ECCO Working Group [Dietitians of ECCO]

Abstract: Although the current doctrine of IBD pathogenesis proposes an interaction between environmental factors and gut microbiota in genetically susceptible individuals, dietary exposures have attracted recent interest and are, at least in part, likely to explain the rapid rise in disease incidence and prevalence. The D-ECCO working group along with other ECCO experts with expertise in nutrition, microbiology, physiology, and medicine reviewed the evidence investigating the role of diet and nutritional therapy in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 184 publications
1
88
0
4
Order By: Relevance
“…A normal, unrestricted diet in line with national healthy eating guidelines should be the final goal of therapy when food is reintroduced . Limited data propose three dietary options for food reintroduction: an unrestricted diet, an exclusion/elimination diet, and a low‐fat/fiber exclusion diet; however, it is unclear whether particular dietary components actually influence the success of food reintroduction after EEN therapy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A normal, unrestricted diet in line with national healthy eating guidelines should be the final goal of therapy when food is reintroduced . Limited data propose three dietary options for food reintroduction: an unrestricted diet, an exclusion/elimination diet, and a low‐fat/fiber exclusion diet; however, it is unclear whether particular dietary components actually influence the success of food reintroduction after EEN therapy …”
Section: Resultsmentioning
confidence: 99%
“…Four published adult studies have used PEN to induce or maintain remission. The results are conflicting and limited by high dropout rates, different PEN regimens, and lack of control groups . In pediatric and young adult CD cohorts, small studies have reported PEN with an exclusion diet to be effective in remission induction (70%) and maintenance of remission compared to an unrestricted diet (36.4 vs 64% relapse rate, respectively) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with active Crohn's disease (CD) are at greatest risk of undernutrition, particularly the newly diagnosed [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Diet is one of the major determinants of the gut microbiome, and several epidemiological studies have found both positive and negative associations between various dietary constituents and IBD [16]. Among them, higher consumption of soluble fiber (derived from fresh fruits and vegetables), vitamin D, zinc, and potassium had a protective effect against CD.…”
mentioning
confidence: 99%